Requirements Engineering and Process Improvement in Small Software Companies - Kabaale, Edward; Mayoka Kituyi, Geoffrey (Business Process Management Journal, 2015)
Requirements Engineering and Process Improvement (REPI) has been used for some time by software companies to achieve high quality software and gain international certification. However, most Ugandan software companies have not yet fully taken it up. In most case requirements it is considered to be for large companies, leaving Small and Medium Enterprises out. Moreover, little research has been conducted to explore how Ugandan software organizations are handling REPI. Consequently, Ugandan software companies have challenges in improving the quality of their software. It is on this basis that this study sought to explore REPI uptake in Ugandan software companies. Four software companies in Uganda participated in the study. Respondents were selected purposively based of a set criterion. A qualitative research design was adapted to involve, document review, openended questionnaires and interviews as the main data collection tools and techniques. The data were themed and analyzed using descriptive statistics. Findings indicate that software companies were involved more in requirements elicitation, analysis and specification than in requirements validation and documentation. The SMEs did not have a defined REPI approach and lacked knowledge about the availability of REPI models. Further, brainstorming, observation and interviews were the main requirement elicitation methods used. The requirements were mainly elicited from clients, users and management. Requirements databases and Word processors were the main tools used to management requirements with little emphasis on CASE tools.
Keywords: Requirements Engineering Process Improvement; Software Engineering; Requirements Elicitation